Efektivitas Keabsahan Kontrak Elektronik Berdasarkan Hukum Positif di Indonesia - Salsabila, Ditiya; Ispriyarso, Budi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The development of the current era is very rapid along with technology. In the field of contract law, there is a term of electronic contract. The purpose of this research is the effectiveness of the implementation of legality and optimization of electronic contract arrangements based on positive law provisions. The research method used in this study includes normative juridical legal research. Also used statute approach method and conceptual approach. This study uses secondary data which consists of legal materials used in primary legal materials in the form of applicable laws and regulations, secondary legal materials, and tertiary legal materials. This study uses a descriptive qualitative analysis technique. The legal basis governing electronic contracts in Indonesia is the Electronic Information and Transaction Law, Government Regulation Number 24 of 2018, Government Regulation Number 71 of 2019, and Government Regulation Number 80 of 2019. The implementation of electronic contract has not yet been implemented to achieve legal objective for the parties and the application of the validity of electronic contracts is still lacking on several sides.